Journal of paleontology. - Cushman, Joseph A. 1881-1949.; Moore, Raymond Cecil, 1892-; Reeside, John B. 1889-1958; Cooke, Charles Wythe, 1887-; Newell, Norman Dennis, 1909-; Weller, J. Marvin 1899-; Thalmann, Hans Ernst.
Vols. 7-10, 12-13, 15-<17> include section "Bibliography and index to new genera, species and varieties of Foraminifera" (varies) by H. E. Thalmann.